Robust and recyclable magnetic nanobiocatalysts for extraction of anthocyanin from black rice. (1st December 2021) - Yi, Jianhua; Qiu, Manyan; Zhu, Zhenbao; Dong, Xinling; Andrew Decker, Eric; McClements, David Julian
Highlights: Nanobiocatalysts were prepared by attaching cellulase and amylase to magnetic nanoparticles. Immobilized enzymes had better catalytic activity and stability than free enzymes. The nanobiocatalyst was used for extracting anthocyanin from black rice. The nanobiocatalyst exhibited excellent reusability for anthocyanin extraction. Abstract: Anthocyanins, which are natural pigments and nutraceuticals, can be extracted from plant materials using enzyme-assisted methods. However, the enzymes used are often expensive, fragile, and hard to recover/reuse. In this study, cellulase and α-amylase were immobilized on amino-functionalized magnetic nanoparticles to prepare a magnetic nanobiocatalyst. The enzymes in this nanobiocatalyst exhibited higher stability and greater catalytic activity than free enzymes, including good thermal stability (50 to 70℃) and pH stability (pH 4.5–7.5). Nanobiocatalyst efficacy was demonstrated by extracting anthocyanins from black rice, with a maximum yield of 266 mg anthocyanin/100 g black rice obtained. After six reuse cycles, cellulase and α-amylase retained around 70% and 64% of their activity, respectively. Immobilization also increased their reusability. In summary, a novel magnetic nanobiocatalyst was developed for extracting anthocyanins from black rice, which may also have other applications within the food industry.